2015
DOI: 10.5539/sar.v4n4p27
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short-term Tillage of a Long-term No-Till Land on Available N and P in Two Contrasting Soil Types

Abstract: The effects of short-term (4 years) tillage (hereafter called reverse tillage [RT]) of land previously under long-term (29 or 30 years) no-till (NT), with straw management (straw removed [SRem] and straw retained [SRet]) and N fertilizer rate (0, 50 and 100 kg N ha There was no significant effect of RT and straw on ammonium-N, nitrate-N and extractable P in soil. Ammonium-N in soil increased significantly (but small) with N rate in many cases at both sites. Nitrate-N in soil increased with increasing N rate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Proposing that this theory is flawed, our results suggest that correcting for the most critical yieldlimiting factor (i.e., in our case fungal disease management) could serve as a conservative approach to improve yields. Similarly, previous research found that integrated agronomic practices such as N rate and fungicide (de Oliveira Silva et al, 2020a), tillage and N rate (Dyck et al, 2015), sowing date and N rate (Ehdaie & Waines, 2001), plant density and genotypes (Laghari et al, 2011), could efficiently help to meet plant nutrient requirements and increase wheat yields in dryland environments (de Oliveira Silva et al, 2020a;Raza & Saleem, 2013).…”
Section: Impacts Of Agronomic Practices On Grain Yield and Uptake Of N P K And Smentioning
confidence: 77%
“…Proposing that this theory is flawed, our results suggest that correcting for the most critical yieldlimiting factor (i.e., in our case fungal disease management) could serve as a conservative approach to improve yields. Similarly, previous research found that integrated agronomic practices such as N rate and fungicide (de Oliveira Silva et al, 2020a), tillage and N rate (Dyck et al, 2015), sowing date and N rate (Ehdaie & Waines, 2001), plant density and genotypes (Laghari et al, 2011), could efficiently help to meet plant nutrient requirements and increase wheat yields in dryland environments (de Oliveira Silva et al, 2020a;Raza & Saleem, 2013).…”
Section: Impacts Of Agronomic Practices On Grain Yield and Uptake Of N P K And Smentioning
confidence: 77%
“…This information is needed, since there is very limited research on the effects of tillage of previously long-term NT soil on crop yield and nutrient uptake, soil fertility, and persistence of organic C in soil that was gained/stored under NT on individual farm fields (Lal et al, 1990;Campbell et al, 1988Campbell et al, , 1996Campbell et al, , 1998Hassink, 1997;Yang & Kay, 2001a;Six et al, 2002b;Vandenbygaart & Kay, 2004;Baan et al, 2009), especially in the Parkland region of western Canada where large quantities of crop residue are produced and left on land after harvest. The objectives of this study were to examine the effects of short-term (2 or 3 years) pre-seeding shallow tillage (hereafter called reverse tillage -RT) of land previously under long-term NT (29 or 30 years) on crop yield and nutrient uptake [seed and straw yield, N and P uptake in seed and straw of annual cereals/oilseeds]; soil quality [total organic C (TOC) and N (TON), light fraction organic C (LFOC) and N (LFON) and mineralizable N (N min ) in the 0-7.5 and 7.5-15 cm soil layers]; and soil fertility [nitrate-N, ammonium-N, extractable P, exchangeable K and sulphate-S in the 0-7.5, 7.5-15 and 15-20 cm soil layers] in two contrasting soil types (a Gray Luvisol soil at Breton and a Black Chernozem [Albic Argicryoll] soil at Ellerslie, Alberta, Canada; Dyck et al, 2015Dyck et al, , 2016. This paper discusses the effects of RT on soil quality parameters, related to quantity and quality of soil organic C and N.…”
Section: Introductionmentioning
confidence: 99%